c - Lee, Jeong-suk (Seoul: 4&books, 2012)
'How can I go to the desolate land of the Lord?' 'I am going to be ahead of you.' A diary of a missionary in his seventies who overcame a tough marriage and immigration life, I walked to the diary of my life, one by one, and there remained the blessing of God who went ahead of me in suffering and my thanks to him. God always gave me love in my life like a grasshopper. "--Google Books
In Korean.
Keywords: Christian life; Missionaries -- Biography -- Korea